THE INFLUENCE OF LIQUIDITY AND LEVERAGE RATIO ON SHARE PRICES OF THE PHARMACEUTICAL SUB-SECTOR LISTED ON THE INDONESIAN STOCK EXCHANGE FOR THE PERIOD 2016-2020 - mariyani, dede (JEA17: Jurnal Ekonomi Akuntansi, 2023)
This research aims to determine the effect of Liquidity and Leverage Ratios on share prices in the pharmaceutical sub-sector listed on the Indonesia Stock Exchange for the 2016-2020 period. The sample in this study consisted of 8 pharmaceutical sub-sector companies on the Indonesia Stock Exchange (BEI) in the 2016-20120 research period which were selected based on certain criteria using the purposive sampling method. The data analysis used in this research is multiple linear regression analysis processed with SPSS 26. From the multiple regression model used in this research, the regression equation is obtained, namely Y= 4000.998 - 324.194 (CR) - 549.615 (DER) + e. Based on the test results, it shows that partially the Liquidity variable which is measured using the Current Ratio (CR) has a negative and insignificant effect on stock prices, Leverage which is measured using the Debt to Equity Ratio (DER) has a negative and significant effect on the stock prices of listed pharmaceutical sub-sector companies on the Indonesian Stock Exchange for the 2016-2020 period.